2018
DOI: 10.1200/jco.2017.76.1825
|View full text |Cite|
|
Sign up to set email alerts
|

Pain Management in Cancer Center Inpatients: A Cluster Randomized Trial to Evaluate a Systematic Integrated Approach—The Edinburgh Pain Assessment and Management Tool

Abstract: Purpose Pain is suboptimally managed in patients with cancer. We aimed to compare the effect of a policy of adding a clinician-delivered bedside pain assessment and management tool (Edinburgh Pain Assessment and management Tool [EPAT]) to usual care (UC) versus UC alone on pain outcomes. Patients and Methods In a two-arm, parallel group, cluster randomized (1:1) trial, we observed pain outcomes in 19 cancer centers in the United Kingdom and then randomly assigned the centers to either implement EPAT or to cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Importantly, symptom monitoring interventions can improve symptom management, enhance QOL, and prevent hospitalizations among patients with cancer [11][12][13][14]. Prior investigations have focused primarily on patients in the outpatient setting, yet a recent study showed that a pain assessment and management intervention for hospitalized patients with cancer could improve pain outcomes in the inpatient setting [14]. However, this study did not address other important physical and psychological symptoms, which can impact patient outcomes in the inpatient setting [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, symptom monitoring interventions can improve symptom management, enhance QOL, and prevent hospitalizations among patients with cancer [11][12][13][14]. Prior investigations have focused primarily on patients in the outpatient setting, yet a recent study showed that a pain assessment and management intervention for hospitalized patients with cancer could improve pain outcomes in the inpatient setting [14]. However, this study did not address other important physical and psychological symptoms, which can impact patient outcomes in the inpatient setting [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients' symptom burden represents a modifiable risk factor that, if properly addressed, may improve patient outcomes. Importantly, symptom monitoring interventions can improve symptom management, enhance QOL, and prevent hospitalizations among patients with cancer [11][12][13][14]. Prior investigations have focused primarily on patients in the outpatient setting, yet a recent study showed that a pain assessment and management intervention for hospitalized patients with cancer could improve pain outcomes in the inpatient setting [14].…”
Section: Introductionmentioning
confidence: 99%
“…A recently published study illustrates the design and conduct of a cluster randomized trial to test a multilevel intervention to improve symptom management. In this study, 19 cancer inpatient units were randomly assigned to implement a clinician-delivered bedside pain assessment and management tool or to continue with usual care [17]. The effects of the intervention were tested by comparing changes in the percentages of patients with a clinically significant improvement in their pain at the inpatient unit level.…”
mentioning
confidence: 99%
“…11,12 Whilst an objective approach to nociception may be possible, the assessment and subsequent management of pain remain subjective, and often suboptimal, even with the use of defined protocols and guidelines. 13 Education of healthcare staff and improved understanding of what factors affect clinical decision-making around analgesia are explored using neuroimaging. Empathy and risk taking were shown to be some of the factors impacting on how patients with pain were managed in the emergency department.…”
mentioning
confidence: 99%